Curcumin and Epigallocatechin Gallate Inhibit the Cancer Stem Cell Phenotype via Down-regulation of STAT3–NFκB signaling - Chung, Seyung S. (Anticancer Res, 2015)
BACKGROUND/AIM: The cancer stem cell (CSC) model postulates the existence of a small proportion of cancer cells capable of sustaining tumor formation, self-renewal and differentiation. Signal Transducer and Activator of Transcription 3 (STAT3) signaling is known to be selectively activated in breast CSC population. However, it is yet to be determined which molecular mechanisms regulate STAT3 signaling in CSCs and what chemopreventive agents are effective for suppressing CSC growth. The aim of this study was to examine the potential efficacy of curcumin and epigallocatechin gallate (EGCG) against CSC and to uncover molecular mechanisms of their anticancer effects. MATERIALS AND METHODS: To suppress CSC phenotype, MDA-MB-231 and MCF7 cells transfected with human epidermal growth factor receptor 2 (HER2) breast cancer cell lines were treated with curcumin (10 μM) with/without EGCG (10 μM) for 48 hours. We used tumor-sphere formation and wound-healing assays to determine CSC phenotype. To quantify CSC populations, Fluorescence-activated cell sorting profiling was monitored. STAT3 phosphorylation and interaction with Nuclear Factor kB (NFkB) were analyzed performing western blot and immunoprecipitation assays. RESULTS: Combined curcumin and EGCG treatment reduced the cancer stem-like Cluster of differentiation 44 (CD44) positive cell population. Western blot and immunoprecipitation analyses revealed that curcumin and EGCG specifically inhibited STAT3 phosphorylation and STAT3-NFkB interaction was retained. CONCLUSION: This study suggests curcumin and EGCG function as antitumor agents for suppressing breast CSCs. STAT3 and NFκB signaling pathways could serve as targets for reducing CSCs leading to novel targeted-therapy for treating breast cancer.